Problems of Teaching Arabic Language to non-native speakers and its methodological solutions - Mohd. Shamsuddin, Salahuddin; Hj. Ahmad, Siti Sara Binti (Advances in Social Sciences Research Journal, 2019)
Teaching Arabic to non-Arabs in non-Arab Islamic countries, especially in South-East Asia, is different to Arabs in their Arab countries. Arab environment differs to the non-Arab environment, because Arabic is taught in the Arab countries as a national language, while it is not taught in non-Arab Islamic countries as a foreign language. We sanctify Arabic as the language of the Holy Qur’an, the language of Muḥammad the Prophet and the language of Islamic heritage written in the standard Arabic. We study Arabic for the religious purposes. Therefore, we try to study some issues related to Arabic textbooks in South East Asia to see the differences between the teaching Arabic in its native environment and Malay environment and the appropriateness of teaching methods in Arab environment to the nature of students of Arabic in Malay environment. This paper aims to search the solution of the problems related to the teaching Arabic, its challenges and obstacles that impede its education in this region are similar. However, the methods of teaching Arabic must be developed by the modern linguistics and advanced theories of teaching, ​​and their suitability for teaching Arabic language, so that it can regain its suitable place among the world’s languages.